Impact of general versus epidural anesthesia on early post-operative cognitive dysfunction following hip and knee surgery - Mandal, Sripurna (Medknow Publications, 2011)
BACKGROUND: Post-operative cognitive dysfunction is the subtle cerebral complication temporally seen following surgery. The aim of this study was to compare the influence of either general anesthesia (GA) or epidural anesthesia (EA) on the early post-operative neurocognitive outcome in elderly (>59 years) subjects undergoing hip and knee surgery. METHODS: A total of 60 patients were recruited in a prospective, randomized, parallel-group study, comparable by age and sex. They were enrolled and randomized to receive either EA (n = 30) or GA (n = 30). All of them were screened using the Mini Mental State Examination (MMSE), with components of the Kolkata Cognitive Screening Battery. The operated patients were re-evaluated 1 week after surgery using the same scale. The data collected were analyzed to assess statistical significance. RESULTS: We observed no statistical difference in cognitive behavior in either group pre-operatively, which were comparable with respect to age, sex and type of surgery. Grossly, a significant difference was seen between the two groups with respect to the perioperative changes in verbal fluency for categories and MMSE scores. However, these differences were not significant after the application of the Bonferroni correction for multiple analyses, except the significant differences observed only in the MMSE scores. CONCLUSIONS: We observed a difference in cognitive outcome with GA compared with EA. Certain aspects of the cognition were affected to a greater extent in this group of patients undergoing hip and knee surgery.